The distribution network - risk factors from the perspective of the flagship enterprise - Marzena Kramarz; Włodzimierz Kramarz (Polityki Europejskie, Finanse i Marketing)
The aim of the study presented in the paper was to identify the key factors which are the source of interference and cause deviations in material flows. Disturbances in material flows, reducing the efficiency of entire supply chains and the efficiency of individual chain links, are treated as risk factors The realization of distributional tasks based on the internal resources and the resources of network partners is, on one hand, an opportunity to adapt to market changes and create innovative products and services, yet, on the other hand, it increases enlarges the complexity of the system and is a source of interference in material flows. Also, the complexity of the network increases together with the growth of the differentiation of the realized tasks. Consequently, distributional enterprises' taking over tasks connected with the differentiation of base products according to the needs reported by the customers (postponed production tasks) also increases the risk of disturbances in material flows.